HOW TECHNOLOGY IS TRANSFORMING THE INDUSTRY OF TOURISM (Multidisciplinary Journal of Science and Technology, 2025)
One of the fastest growing sectors is certainly tourism and hospitality industry. This article is going to outline a brief history of tourism, the integration of smart technologies like artificial intelligence, virtual reality, digital booking platforms etc. into the tourism sector and how it is affecting visitors’ overall experience and their choice of tourist destination, potential opportunities and challenges that technology can create, with data security and over-reliance being the main ones. Special attention is given to South Korea as an example, a country that was able to boost it’s tourism further with the integration of so-called technologies. In conclusion, this article would give certain recommendations to and tourism organizations on adopting technology in a way that can benefit both tourists and nationals.